METAVERSE AND ITS IMPLICATION IN LAW AND BUSINESS - Johan, Suwinto (Jurnal Hukum Progresif, 2022)
We hear that the future world is the world of the Metaverse. Metaverse is a virtual space created by digital versions of various aspects of life. This study aims to examine the function of law in the metaverse world. This study uses a normative juridical method. This study concludes that the metaverse world still requires the implementation of different laws. The current laws and regulations need to make implementation adjustments in the metaverse world. The change from the real world to the virtual world is like how communication in the real world becomes digital communication that we are experiencing. Adjustments to human behavior must be accompanied by adjustments to the governing regulations. State boundaries become fictitious, and applicable laws do not recognize state and government boundaries.